The index of microbial air contamination in dental clinics: A review and meta-analysis - Pasquarella, Cesira; Viani, Isabella; Colucci, Maria Eugenia; Pedrazzi, Giuseppe; Affanni, Paola; Zoni, Roberta; Finzi, Maria Chiara; Veronesi, Licia; Albertini, Roberto (Acta Biomedica Atenei Parmensis, 2026)
Background and aim. In dental clinics, the risk of airborne infection is relevant. Active and passive sampling can be used to assess microbial air contamination. Passive sampling has been standardised by the Index of Microbial Air contamination (IMA). This study aimed to review the use of the IMA standard for air quality assessment in dental clinics, before, during and after dental procedures, and to conduct a meta-analysis of the obtained values. Methods. Scopus, PubMed, and Web of Science were analyzed for articles published until 2024, citing “Pasquarella C., et al., The index of microbial air contamination. J Hosp Infect 2000”. Only original studies, in English or Italian, performed in dental clinics and applying the IMA standard were included in the review. Results. After applying the inclusion criteria, nine studies were considered. The mean IMA values before, during, and after dental procedures ranged from 2.4 to 38.3, 19 to 53.3, and 13 to 20, respectively. Seven studies were included in the meta-analysis, which yielded mean IMA values of 15.4, 32.7, and 16.7, before, during and after dental activity, respectively. Considering only the study performed in Europe, a value of 29 IMA during the dental activity was obtained. Conclusions. This review has given a picture of the use of the IMA standard in dental clinics. The meta-analysis yielded IMA values, before, during and after clinical practice, which could be valuable in clinical practice. Due to the ease of use, low cost, and comparability of results, the IMA standard is recommended for the routine monitoring of microbial air contamination (www.actabiomedica.it).